Fortification of the Nutritive Value of Mushroom (Termitomyces microcarpus) with Paw-Paw Leaf Meal for Broiler Chicks Diet - Ebenebe, C.I.; Itefue, O.; Ebere-Ohameje, T.C.; Okonkwo, J.C. (Pakistan Journal of Nutrition, 2011)
The effect of fortifying the nutritive value of mushroom with paw-paw leaf meal in the diet of broilers was studied using one hundred and eight day old chicks. Three diets were formulated, the first which served as control had no mushroom (Diet A) and the second diet had 2% mushrooms (Diet B) while the third had 2% mushroom and 2% paw-paw leaves (Diet C). Thirty-six broiler chicks were randomly assigned to each of the three dietary at the rate of twelve chicks per replicate and three replicates per experimental unit in a Completely Randomized Design (CRD). Beside feed trail period, the experiment lasted for five weeks. During this period, the birds were subjected to similar husbandry and sanitation practices; daily records of food intake and weekly record of weight gain were taken. Data obtained were subjected to ANOVA appropriate for Completely Randomized Design and the differences between means were separated using Least Significant Differences (LSD). The result showed that birds fed with control diet had the highest feed intake of compared to those fed Diet B and Diet C. Broiler chicks on Diet C however had the highest records in all the productive indices (weight gain, specific growth rate and food conversion ratio) investigated. The study therefore recommends inclusion of at least 2% paw-paw leaf meal in broiler chicks’ diet that contains mushroom.